STUDENT’S RESPONSE TO PHYSICS HANDOUTS BASED ON ANDROID AS LEARNING MEDIA ON THE TOPIC OF ALTERNATIVE CURRENT (AC) - Dahliana; Agustina, Eeiss; Azizah, Nadia; Yuliani, Hadma (Universitas Tadulako, 2022)
This research aims to find out the student's responses to physics handouts based on android as a learning media on the topic of alternating current (AC). Data were collected by questionnaires to describe as quantitative descriptive research. The data were described in a rating scale as in the Likert Scale obtained from the provision of 25 questions that were distributed to students privately. According to the result, the average assessment showed a percentage of 82.32% in the excellent category. So, the implications suggested that physics handouts based on android had received a good response based on the questionnaires and have been valid as a learning media.